A Quick Glance at Numerical Modeling in Obstructed Human Airway - Nasrul Hadi, Johari; Zulkifli, Ahmad@Manap; Syifak Izhar, Hisham (2012)
This quick glance focuses on the analysis of flow behavior in the obstructed human airway by the numerical approach. It is shown that the understanding of flow behavior in a patient with tracheal stenosis is imminent to the biomechanics knowledge, and the numerical study is accepted to be effective in some ways. Several current researches have initiated the new algorithm and numerical schemes, which produce significant result. This quick glance review content is divided into three sections which are based on the three research questions. The first research question is the capability of simplified and realistic model derived from CT scan images in simulating breathing flow. For the second research question, what is the behavior of flow parameters inside the trachea and main bronchi with the presence of tracheal stenosis; will review about description of tracheal stenosis disease, classification of tracheal stenosis and the factors involved, and studies of flow in the obstructed airways. The third research question, what is the correlation between the factors of location and size of tracheal stenosis to the outcomes of possible breathing difficulties